Pengembangan Kurikulum Bahasa Arab di Sekolah Islam Terpadu SMP Luqmanul Hakim Aceh - Aisyam Mardliyyah; Tulus Musthofa (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2020)
Sekolah Islam Terpadu (SIT) or Integrated Islamic Schools are essentially schools that implement concepts. Islamic education is based on the Qur'an and Sunnah and is based on the National Education System Law. This article aims to describe and find out the curriculum components and curriculum organization in the Integrated Islamic School, especially in Arabic subjects at Luqmanul Hakim Aceh Integrated Islamic Middle School. The research method used was literature study (library research) with documentation and interview collection techniques and for its analysis using descriptive analysis. The results showed that the curriculum components in SIT are Objectives, Content, Process and Evaluation of Curricula that have TERPADU characteristics (Telaah/Study, Eksplorasi/Explore, Rumuskan/Formulate, Presentasikan/Present, Aplikasikan/Apply, Duniawi/Worldly, Ukhrowi/Divinity). Overall curriculum organization under the auspices of the JSIT institute of Arabic subjects at all levels and general subjects at elementary through junior high level can be classified in the curriculum organization of broad field curriculum, while general subjects at the level of senior high school belong to the curriculum organization of separated-subject. In its implication the SIT curriculum can be categorized into Integrated Curriculum. Keywords: Curriculum Development, Arabic Curriculum, Integrated Islamic School.